Physico-chemical attributes and correlation among grain quality traits of some exotic aromatic rice lines (Journal of the Bangladesh Agricultural University, 2014)
Forty three rice genotypes were used to evaluate their aroma detection through sensory test. Aroma was detected by 1.7% KOH as a sensory test. Thirteen rice genotypes were detected having strong aroma; ten had moderate aroma; fifteen had slight aroma and five had no aroma. In case of grain shape study, 37 genotypes were evaluated as slender and six as medium. In this study, grain aroma had significant and positive association with grain length width ratio; significant and negative association with grain width, significant and negative association with gelatinization temperature, and significant and negative association with grain length. Gelatinization temperature had significant and negative correlation with grain length, significant and negative association with grain length width ratio, significant and positive association with grain width. Grain length had significant and negative correlation with grain width; significant and positive correlation with length width ratio. Grain width had significant and negative correlation with length width ratio. Finally, it can be concluded that among 43 genotypes Basmati370,CT19541-13-3-1-2P- 1P,PSBRC18,PSB-RC2(IR32809-26-3-3),IR64,IR50,2001059-TR2151-6-1-1,IR64-P401,IR72-P204 were found good grain quality traits having higher physico-chemical attributes. These elite lines could be readily used in breeding programmes to improve grain quality traits. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19899 J. Bangladesh Agril. Univ. 11(2): 227-232, 2013